THE LONGEVITY IN THE DOWN SYNDROME (Fiep Bulletin - online, 2013)
The Down syndrome was described for the first time in 1866 and, although the many evolutions that already had occurred, still is considered a recent discovery. Treatments, therapies and diverse forms of stimulation for the carrier of the syndrome have been developed, what it has been basic for its better motor development and magnifying of its social performance. The life expectancy in Brazil increased in recent years, exceeding the age band of 70 years, as main consequence of the constant evolution of the health, either in the national or international scope. The objective of this study was to analyze the longevity of the carriers of Down syndrome to verify if the life expectancy of this specific group follows the national trend of aging. For the accomplishment of this work, a literary revision was become fulfilled on the thematic one, through recent books and articles on the Down syndrome (DS). They had been gotten given excellent being that, some studies as the carried through ones for the CEPEC (Center of Studies and Clinical Research of Sao Paulo), demonstrate the existence of carriers of DS who had exceeded the 50 and 60 years, following the improvement in the world-wide health in such a way how much the Brazilian. As parameter, given on the longevity of the carrier they point that the life expectancy was around 40 years, being that in the decade of 20, this perspective was scramble for 9 the 10 years. One concludes that the expectation for carriers of the Down syndrome increased even so not if it has stories of as either the relation longevity or quality of life for these people. Since the clinical treatments have reached resulted promising, the perception of quality of life of the carriers is intended to evaluate which a time that today babies whom syndrome of Down has, can grow healthy and active.
Keywords: Down syndrome; Carrier; Longevity